(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the importance of modern pedagogical technologies and the teachings of Eastern thinkers in the education of preschool children from a scientific and theoretical perspective. At the same time, it is emphasized that combining the spiritual heritage of Eastern thinkers with modern pedagogical technologies is an important factor in the formation of high spiritual and moral qualities in children, and in the upbringing of a well-rounded person who can think independently and creatively.